2018
DOI: 10.1093/jscr/rjy188
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis caused by acute phlegmonous gastritis based on a group A Streptococcus

Abstract: We present a case of 45-year-old male with acute phlegmonous gastritis (APG) based on a hemolytic group A Streptococcus. APG is a rare and often a potentially fatal disease, which is characterized by a severe bacterial infection of the gastric wall. Because APG is a rapidly progressive disease, it comes with high mortality rates. Patients with an early diagnosis may undergo successful treatment and have a survival benefit. As soon as the diagnosis of APG is suspected, aggressive and adequate antibiotic treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Table 2 summarizes cases of acute phlegmonous gastritis published between 2010 and 2019 caused by S. pyogenes . 1 , 8 , 9 , 14 20 In this review, 10 published cases showed: (a) the worldwide distribution of the disease, (b) the manifestation of STSS associated with septic shock and multi-organ failure (8/10), and (c) the high mortality rate associated with the disease (3/10 deaths). In three of the cases, the responsible microorganism was isolated from the blood while gastrectomy was necessary for four patients.…”
Section: Discussionmentioning
confidence: 92%
“…Table 2 summarizes cases of acute phlegmonous gastritis published between 2010 and 2019 caused by S. pyogenes . 1 , 8 , 9 , 14 20 In this review, 10 published cases showed: (a) the worldwide distribution of the disease, (b) the manifestation of STSS associated with septic shock and multi-organ failure (8/10), and (c) the high mortality rate associated with the disease (3/10 deaths). In three of the cases, the responsible microorganism was isolated from the blood while gastrectomy was necessary for four patients.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, upper endoscopy revealed areas of tissue necrosis and exudate leading to the provisional diagnosis of PG. The diffuse type of PG has been characterized by dark red and diffuse gastric wall thickening, which can cause gastric cavity expansion and gastric wall perforation, thus requiring urgent intervention [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors include alcoholism, achlorhydria, immunosuppression and diabetes mellitus. 3,5,6 However, the exact mechanism of PG is still unknown. Fifty percent of patients have no preexisting risk factors.…”
Section: Phlegmonous Gastritis: An Unusual Mimic Of Gastric Cancermentioning
confidence: 99%
“…5 Better outcomes arise with prompt administration of antibiotic therapy coupled with early surgical resection. 6 PG is often confirmed retrospectively on histopathological analysis post-operatively warranting a greater suspicion for this lifethreatening disease. Presentation as a gastric malignancy mimic as in this case and these non-specific symptoms may further complicate and delay diagnosis.…”
Section: Phlegmonous Gastritis: An Unusual Mimic Of Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation